Analysis of Claim Handling Procedures for Prucinta Products at PT. Prudential Life Assurance Binjai - Shalsa Sakila; Tri Inda Fadhila Rahma (Penerbit Jurnal Indonesia, 2022)
This artcle ams to determne the producere for mplementng clams handlng at PT.Prudental Prudental Lfe Assurance Bnja. Ths research s a descrptve research wth a qualitative approach. Data collecton technques used are ntervews wth nsurance agents PT Prudental Lfe Assurance Bnja and lterature study. Based on the results of research and dscusson, conclusons have been drawn. An nsurance clam s a clam from the nsured party n connecton wth a contract agreement between the nsurance and the nsured party, where each party bnds tself to guarantee the payment of compensaton by the nsurer f the nsurance premum payment has been made by the nsured party, when a dsaster s suffered by the nsured party. As for the stages of the clam beng submtted, t must be completed wth all the requred complementary requrements and documents. f the requrements and documents are not complete, there wll be a rejecton from the nsurance company.